Ludo-narrativism as Bogost’s proceduralism in the light of the ludology-narratology debate - Petrowicz, Marcin (Replay. The Polish Journal of Game Studies, 2014)
The ludology-narratology dispute has been dismissed and neglected by many researchers. Theorists on both sides of the conflict created theories assimilating the concepts of their opponents. However, in my opinion, Ian Bogost — a scientist not involved in the dispute — has the most interesting solution to the problem. Bogost’s basic concepts — unit operations comparative criticism and procedural rhetoric theory – combine interpretations of game rules with those of narratives. The achievements of Bogost seem less known and appreciated in the Polish game studies. In this article, I will present the basic theories from Bogost’s main books: Unit Operations: An Approach to Videogame Criticism and Persuasive Games: The Expressive Power of Videogames in the context of ludology versus narratology debate.